Regulating the sharing economy - Kristofer Erickson; Inge Sørensen (Internet Policy Review, 2016)
In this introductory essay, we explore definitions of the 'sharing economy', a concept indicating both social (relational, communitarian) and economic (allocative, profit-seeking) aspects which appear to be in tension. We suggest combining the social and economic logics of the sharing economy to focus on the central features of network enabled, aggregated membership in a pool of offers and demands (for goods, services, creative expressions). This definition of the sharing economy distinguishes it from other related peer-to-peer and collaborative forms of production. Understanding the social and economic motivations for and implications of participating in the sharing economy is important to its regulation. Each of the papers in this special contributes to knowledge by linking the social and economic aspects of sharing economy practices to regulatory norms and mechanisms. We conclude this essay by suggesting future research to further clarify and render intelligible the sharing economy, not as a contradiction in terms but as an empirically observable realm of socio-economic activity.
Keywords: 300; Sharing economy; Peer-to-peer (P2P); Crowd-sharing